Vidas em trânsito: ascensão financeira e o enredo identitário que aprisiona na condição liminar - sorveteiros ítalo-brasileiros entre Itália, Alemanha e Brasil como (não) lugares - Portugueis, Diane (2018)
Our focus is to investigate how the process of constitution, metamorphosis and identity rearrangement is organized, from the perspective of liminality, a condition individuals encounter on their paths in the quest for greater financial autonomy. We also strive to understand the crisis inherent to their whereabouts while travelling between different living spaces, in different countries. Our subjects are Italian-Brazilians who work in ice-cream parlors in Germany. These are young people who have been encouraged to acquire an Italian passport through the network in place between the cities of Urussanga (State of Santa Catarina, Southern Brazil) and Longarone, Italy, which enables them to be recruited, trained for jobs at these gelaterias, and then later sent to Germany. They develop relationships with these different countries, since they continue to visit their hometowns, where they buy property with the intent to come back permanently one day. We address issues related to the relationships that are built with these countries: inclusion/exclusion, the creation of subjectivities, forms of oppression and identity politics. In this thesis, we address how these individuals deal with living life between places and how this changes their identities. The methodology chosen for data collection was the life story narratives, which have been analyzed based on the identity-metamorphosis-emancipation phrase proposed by Antônio da Costa Ciampa, as well as multi-situated ethnographies and interviews. The past, the present, as well as identity politics all become intertwined in the projects of these ice-cream parlor workers creating a living space that lies between (no) places. These configurations arise due to a constant lack of definition regarding their status, triggered by the socioeconomic, historical and political relationship in which they were socialized and that they recreate, leading to permanent liminality